The question of future hope in 2 Kgs 25.27–30 and the book’s dynastic framework in 1 Kgs 1.1–53 and 2 Kgs 11.1–20 - Tafferner, Mario (Journal for the study of the Old Testament, 2024)
The present study revisits the question of future hope in the Book of Kings by inquiring into appropriate intertexts for interpreting the report of Jehoiachin’s release from prison in 2 Kgs 25.27–30. As will be demonstrated, this passage shares the literary motif of ‘two contestants struggling for a throne’ (כסא‎) with both 1 Kgs 1.1–53 and 2 Kgs 11.1–20. These three accounts occupy structurally important positions within the book (beginning, climax, end) and use this motif to communicate Davidic dynastic permanence.